Epitaxial Growth of 6 in. Single‐Crystalline Graphene on a Cu/Ni (111) Film at 750 °C via Chemical Vapor Deposition. Issue 22 (3rd April 2019) - Zhang, Xuefu; Wu, Tianru; Jiang, Qi; Wang, Huishan; Zhu, Hailong; Chen, Zhiying; Jiang, Ren; Niu, Tianchao; Li, Zhuojun; Zhang, Youwei; Qiu, Zhijun; Yu, Guanghui; et al.
Abstract: The future electronic application of graphene highly relies on the production of large‐area high‐quality single‐crystal graphene. However, the growth of single‐crystal graphene on different substrates via either single nucleation or seamless stitching is carried out at a temperature of 1000 °C or higher. The usage of this high temperature generates a variety of problems, including complexity of operation, higher contamination, metal evaporation, and wrinkles owing to the mismatch of thermal expansion coefficients between the substrate and graphene. Here, a new approach for the fabrication of ultraflat single‐crystal graphene using Cu/Ni (111)/sapphire wafers at lower temperature is reported. It is found that the temperature of epitaxial growth of graphene using Cu/Ni (111) can be reduced to 750 °C, much lower than that of earlier reports on catalytic surfaces. Devices made of graphene grown at 750 °C have a carrier mobility up to ≈9700 cm 2 V −1 s −1 at room temperature. This work shines light on a way toward a much lower temperature growth of high‐quality graphene in single crystallinity, which could benefit future electronic applications. Abstract : A 6 in. high‐quality single‐crystal graphene without wrinkles and contaminations on Cu/Ni (111) film is successfully achieved at 750 °C. The quality of graphene with carrier mobility ≈9700 cm 2 V −1 s −1 is as good as when grown at high growth temperatures, often 1000 °C. This study shines light on the growth of graphene wafers at low temperature and will highly benefit graphene application in electronics.